Pengaruh Pemberian Kompos dan Pupuk NPK terhadap Produktivitas Kedelai (Glycine max (L.) Merril) - ,, Hapsoh; ,, Wardati; Hairunisa, dan (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2019)
The productivity of soybeans (Glycine max (L.) Merril) in Indonesia is still low, and therefore it is necessary to increase productivity through management of soil fertility such as fertilizer application. This study aimed to determine the effect of single compost, NPK, and their interactions on soybean productivity. The study was conducted in the experimental station of the Faculty of Agriculture, Universitas Riau from May to September 2017. The experiment used a factorial design arranged in a randomized block design. The first factor consisted of: without compost, oil palm empty fruit bunch compost (TKKS) and rice straw compost. The second factor consisted of: without NPK fertilizer, NPK dose 125 kg ha-1 and NPK dose 250 kg ha-1. Data analyzed statistically and further evaluation using Duncan’s multiple range test. The single treatment of compost increased the nutrient content of leaf N 3.1%, leaf K 24%, percentage of filled pods 3.45%, number of seeds each plant 14%, seed weight each plant 15% and weight of 100 seeds 3.20%. The single treatment of NPK fertilizer also increased leaf N by 4.67%, leaf P by 9% and leaf K by 4%, number of filled pods as 27%, percentage of filed pods with 5%, number of seeds each plant 29%, seed weight each plant 27%, production each m2 by 26% and weight 100 seeds by 7%. Interactions between treatments increased the levels of N, P, and K and percentage of filled pods. This research provides information for farmers to utilize compost in order to reduce the use of inorganic fertilizers.